Public Awareness and Knowledge of Oral Cancer and its Risk Factors in Lahore City, Pakistan - Salman Amin, Ijaz Ur Rahman, Zeeshan Aslam Jan, Tooba Saeed, Tahmasub Faraz Tayyab, Junaid Amin, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goal of our study is to assess the general public's knowledge and awareness related to oral cancer, its risk factors, and attitude regarding early diagnosis in Lahore city. Material and Method: A cross sectional study was carried out in Lahore City Pakistan in March 2021.Four hundred and twenty-five questionnaires were distributed among Lahore city population and 385 participants responded. Conventional sampling technique was used for participant’s selection. Written inform consent was taken from all participants. Participants greater than 15-year-old were taken in this study. Result: Out of 385 participants 64.2% participants were male and 35.8% were female.10.4 % participants were uneducated and 34.2% participants were graduated.23.3 % participants were smokers.68.9% responders had heard about oral cancer and 31.1 % had not heard about oral cavity cancer.58.5% participants consider that oral cancer can be avoided while 48.7% participants consider that oral cancer is not curable .81.2 % participants said that smoking is a main risk factor for oral cancer and 62.2% participants consider relationship between Alcohol and oral cancer while 22.3% consider no relationship between them. 38.9 %, 25.4%and 39.4% participants were able to identify old age, diet, and sunlight are causative agents of oral cancer respectively .51% participants think that they will go for diagnosis if they find any minor lesion in the oral cavity. CONCLUSION: The current study concluded that people living in Lahore city have a knowledge and awareness about oral cancer and also they think that tobacco and smoking are main risk factors for oral cancer while they have inadequate knowledge about certain risk factors like diet, old age and sunlight. We also recognize that only 51 % people will go for early diagnosis if they found a lesion in the oral cavity. So the cancer prevention educational program in public can increase awareness regarding oral cancer.